Biogeochemical and 16S rRNA gene sequence evidence supports a novel mode of anaerobic methanotrophy in permanently ice‐covered Lake Fryxell, Antarctica. (24th June 2016) - Saxton, Matthew A.; Samarkin, Vladimir A.; Schutte, Charles A.; Bowles, Marshall W.; Madigan, Michael T.; Cadieux, Sarah B.; Pratt, Lisa M.; Joye, Samantha B.
Abstract: Lake Fryxell, McMurdo Dry Valleys, Antarctica contains a constantly cold water column and perennial ice‐cover. Although carbon and sulfur cycling in this amictic lake have been studied previously, a paired investigation of 16S rRNA gene based microbial diversity and geochemistry of Lake Fryxell is lacking. Here, we used a combination of radiotracer‐based rate measurements, geochemical measurements, and molecular microbial community analysis to investigate the anaerobic oxidation of methane (AOM) and associated processes in Lake Fryxell. The results show that while AOM and sulfate reduction appear coupled in the upper regions of the anoxic water column, in deep anoxic waters, where AOM rates are highest, sulfate is unlikely to be the electron acceptor for AOM. Despite significant rates of AOM in these waters, no putative AOM‐associated Archaea or Bacteria were observed. Due to a lack of documented AOM electron acceptors and putative ANMEs, we suggest novel modes of AOM dominate in this extreme environment. First, the notable abundance of the bacterial genus Dehalococcoides suggests that reductive dehalogenation could fuel AOM. Further, taxa of the candidate phylum OP9, the Atribacteria, and the Bathyarchaeota (formerly known as the Miscellaneous Crenarchaeotal Group) both commonly observed at cold methane‐seeps globally, may mediate AOM, possibly using humic acids as electron shuttles, in Lake Fryxell.